Organization model for mobile wireless sensor networks inspired in artificial bee colony - Roberto, Guilherme Freire [UNESP]; Maschi, Luis Fernando Castilho; Pigatto, Daniel Fernando; Branco, Kalinka Regina Lucas Jaquie Castelo; Neves, Leandro Alves [UNESP]; Montez, Carlos; Pinto, Alex Sandro Roschildt (Iop Publishing Ltd, 2015)
The purpose of this study is to find a self-organizing model for MWSN based on bee colonies in order to reduce the number of messages transmitted among nodes, and thus reduce the overall consumption energy while maintaining the efficiency of message delivery. The results obtained in this article are originated from simulations carried out with SINALGO software, which demonstrates the effectiveness of the proposed approach. The BeeAODV (Bee Ad-Hoc On Demand Distance Vector) proposed in this paper allows to considerably reduce message exchanges whether compared to AODV (Ad-Hoc On Demand Distance Vector).